1998
DOI: 10.1111/j.1600-0404.1998.tb05955.x
|View full text |Cite
|
Sign up to set email alerts
|

Low dosage clozapine effects on L-dopa induced dyskinesias in parkinsonian patients

Abstract: A low dose of clozapine appears to be beneficial for patients with L-dopa induced dyskinesias that do not respond to other drugs and therapeutic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Thus, 5-HT 2 antagonists reduce symptoms in PD patients (Henderson et al, 1992) and improve neuroleptic-induced parkinsonism (Bersani et al, 1990;Ikeguchi and Kuroda, 1995). Moreover, low-dose clozapine treatment of PD patients with iatrogenic psychosis reduces motor symptoms (Bonuccelli et al, 1997;Durif et al, 1997;Friedman et al, 1999;Pirelli et al, 1998). Since DA antagonists exacerbate parkinsonian symptoms, it is likely that the high 5-HT 2A affinity of clozapine contributes to the motoric improvement.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…Thus, 5-HT 2 antagonists reduce symptoms in PD patients (Henderson et al, 1992) and improve neuroleptic-induced parkinsonism (Bersani et al, 1990;Ikeguchi and Kuroda, 1995). Moreover, low-dose clozapine treatment of PD patients with iatrogenic psychosis reduces motor symptoms (Bonuccelli et al, 1997;Durif et al, 1997;Friedman et al, 1999;Pirelli et al, 1998). Since DA antagonists exacerbate parkinsonian symptoms, it is likely that the high 5-HT 2A affinity of clozapine contributes to the motoric improvement.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…It may also be effective in decreasing dyskinesias [72], and a few studies have focused on its antidyskinetic effect [93, 94]. However, the hematologic monitoring necessary with clozapine can be burdensome for both the patient and the physician and can limit its usefulness.…”
Section: Symptomatic Treatment Of Dyskinesiasmentioning
confidence: 99%
“…Another 4-month, open-label study in 10 patients with PD taking clozapine (mean dose of 30 mg/d) found that dyskinesia was significantly reduced from baseline after 1 week of treatment (P < 0.05) [50]. There was a greater reduction in dyskinesia after 2 weeks of treatment and the effect persisted through the remainder of the study.…”
Section: Clozapinementioning
confidence: 95%